Determining the key elements of community-based care for women and partners following a stillbirth or second trimester miscarriage: protocol for a realist synthesis - Alexander Edward Heazell; Helen Leach; Sophie Staniszewska; Sarah Hillman; Amy Grove; Rachel Court; Becky MacGregor (BMJ Open)
Introduction Stillbirth and second trimester miscarriage have wide-reaching consequences for women, their partners and their families. There is currently little community-based care provision within the National Health Service for women and partners who have had a stillbirth or second trimester miscarriage. There is a research gap in the evidence to guide best practice. This review will seek to understand how, when and where this care is best delivered.Methods and analysis The aim of this review is to identify the key elements of community-based care following a stillbirth or second trimester miscarriage. As this is a complex intervention, a realist approach will be used to establish for whom, how, when and where this care is best delivered. An initial programme theory will be constructed which will be tested against the available evidence and refined. A wide range of evidence including qualitative, quantitative, mixed-methods and experiential knowledge will be identified through secondary sources, extracted and synthesised to develop and refine the programme theory.Ethics and dissemination This review will not require ethical approval as it does not involve primary data collection. The findings will be submitted for open-access publication to a peer-reviewed journal and disseminated to stakeholders.PROSPERO registration number CRD42024587365.